Phylogenetic relationships and systematics of a subclade of Mesoamerican emerald hummingbirds (Aves: Trochilidae: Trochilini) - Hernández-Baños, Blanca E.; Zamudio-Beltrán, Luz E.; Milá, Borja (Zootaxa, 2020)
Phylogenetic relationships among major hummingbird clades are relatively well resolved, yet due to the lack of morphological synapomorphies and relative phenotypic homogeneity, the systematics of several hummingbird groups remain unresolved. Here, we present the results of a multilocus study of a clade of emerald hummingbirds composed of Cynanthus, Chlorostilbon, Riccordia and Phaeoptila (sensu Stiles et al. 2017). We include taxa not analyzed in previous studies (C. lawrencei, C. auriceps and C. forficatus, from Tres Marías Islands, Western Mexico, and Cozumel Island, respectively), and this allows us to develop a new hypothesis for the phylogenetic relationships within this group. We found that this clade originated in Mesoamerica about 12 million years ago, and comprises four geographically congruent clades: (a) the most basal clade, Phaeoptila sordida, of the Balsas River basin, Mexico; (b) Riccordia bicolor, R. maugaeus, R. ricordii and R. swainsonii of the West Indies; (c) Chlorostilbon assimilis, C. aureoventris, C. melanorhynchus, C. mellisugus, C. poortmani and C. pucherani, all of South America, except C. assimilis of Central America; and (d) a Mesoamerican clade with two Cynanthus subclades: a widespread Mexican clade that includes species formerly belonging to the genus Chlorostilbon: Cynanthus auriceps, C. canivetii, C. doubledayi and C. forficatus; and a clade restricted to the west coast of Mexico and the Tres Marías Islands and composed of C. latirostris and C. lawrencei. Our results help clarify the systematics of this group of emeralds, reconstruct its true evolutionary history, and advance understanding of phenotypic evolution in hummingbirds.